Monsters, Laws of Nature, and Teleology in Late Scholastic Textbooks - Manzo, Silvia (2019)
In the period of emergence of early modern science, 'monsters' or individuals with physical congenital anomalies were considered as rare events which required special explanations entailing assumptions about the laws of nature. This concern with monsters was shared by representatives of the new science and Late Scholastic authors of university textbooks. This paper will reconstruct the main theses of the treatment of monsters in Late Scholastic textbooks, by focusing on the question as to how their accounts conceived nature's regularity and teleology. It shows that they developed a naturalistic teratology in which, in contrast to the naturalistic explanations usually offered by the new science, finality was at central stage. This general point does not impede our noticing that some authors were closer to the views emerging in the Scientific Revolution insofar as they conceived nature as relatively autonomous from God and gave a relevant place to efficient secondary causation. In this connection, this paper suggests that the concept of the laws of nature developed by the new science -as exception-less regularities- transferred to nature's regularity the 'strong' character that Late Scholasticism attributed to finality and that the decline of the Late Scholastic view of finality played as an important concomitant factor permitting the transformation of the concept of laws of nature.